Food and Feeding Habits of Hydrocynus in River Benue Along Mayo Ranewo, Ardo-Kola LGA, Taraba State, Nigeria - Danba Elizabeth Pius; Nokah Juliet; Allahnanan Emmanuel (Darul Yasin Al Sys, 2025)
This study examines the food and feeding habits of Hydrocynus species in River Mayo Ranewo, Ardo-Kola Local Government Area, Taraba State, Nigeria. Hydrocynus, commonly referred to as tigerfish, is a predatory freshwater species of notable ecological and economic value. The research investigates dietary composition, length–weight relationship, and condition factor to better understand the species’ ecological role. Seventy-five specimens were obtained from local fishermen and analyzed in the laboratory. Stomach content analysis revealed seasonal dietary variation, with Tilapia and catfish as predominant prey items, supplemented by decayed fish and fish bones. The length–weight relationship showed a strong positive correlation (R² = 0.99997), indicating isometric growth, while the condition factor (K ≈ 1.20) suggested a healthy population. The results indicate that tigerfish adjust their feeding strategies according to prey availability and environmental conditions. These findings contribute valuable information for sustainable fisheries management and conservation planning, supporting both ecological stability and the economic viability of inland fisheries in Taraba State.